KRITIK ATAS SKEPTISISME EPISTEMOLOGIS PERSPEKTIF TAFSIR JAWADI AMULI - Dani Nur Pajar (Sekolah Tinggi Agama Islam (STAI) Sadra, 2017)
This paper discusses a critical responsse to radical and moderate epistemological skepticism based on skepticism about the credibility of the senses, reason, and the possibility of the existence of the x-factor that manipulates consciousness. The proposed responsse is based on inspiration from the Qur'anic discussion of skepticism through the interpretation of Jawadi Amuli. With Paul Ricoeur's descriptive analysis and hermeneutics, a number of conclusions reached include the following three things. First, according to Jawadi Amuli, the Qur'an views the skepticism of those who reject the truth of the treatise as rooted in epistemological sensibility and ontological materialism, whereas reality is not limited to matter and the senses cannot be a source of belief, but must have reason. Second, radical skepticism is unacceptable, whereas moderate skepticism is acceptable. Third, belief cannot be rejected with skepticism on the senses, reason, as well as on the possibility of the existence of the x-factor that damages consciousness.